E-Commerce Komoditas Berbasis PWA Pada PT.Bejo Agro Lestari Menggunakan Framework Laravel - Yulia Agustina Dalimunthe; David Gladio Situmorang; Septiana Dewi Andriana (Unit Pengelola Jurnal Universitas Harapan Medan, 2022)
PT. Bejo Agro Lestari is a commodity trading business that was founded in early 2019 and operates in the city of Medan. Initially, trade was still limited to coffee commodities, with the terms green beans and roasted coffee, where sales of coffee commodities were B2C or Business to Customer. The problem with the current company is that the use of system still uses conventional methods in making sales to sales. This is less effective because sales are still door to door and use instant messages via WhatsApp, Gmail or consumers come directly to the place of business. How to sell products that are still conventional, it is impossible to increase sales significantly, so from this problem the authors get a solution to solve it, namely by building a PWA-based E-Commerce system on B2C or Business to Customer products with the SDLC Waterfall method, which is expected to provide information commodity products such as green beans and roast beans, which are useful for helping customers find detailed product information such as price and quality, and can easily update coffee product data in real-time using the REST API web service. The application of PWA-based ecommerce is expected to help increase the company’s coffee product sales.